Neutralization of sludge and purification of wastewater from Sindos industrial area of Thessaloniki (Greece) using natural zeolite - Filippidis, A.; Godelitsas, A.; Kantiranis, N.; Gamaletsos, P.; Tzamos, E.; Filippidis, S. (Bulletin of the Geological Society of Greece, 2013)
The commixture of sludge from Sindos industrial area of Thessaloniki with high quality HEU-type natural zeolite (tuff with 86 wt.% clinoptilolite-heulandite) in equal proportions, resulted in odourless and cohesive zeosludge. Also, the treatment of wastewater of pH 7.8 from the same area with high quality HEU-type natural zeolite (88 wt.% clinoptilolite-heulandite) resulted in production of clear water of pH 7.3, free of odours and improved quality parameters by 60% for the NO3 - content, 76% for the chemical oxygen demand (COD), 100% for P2O5 and Cr contents. Simultaneously, a precipitate of odourless and cohesive zeosludge was produced. The odourless and cohesive zeosludge produced either by the commixture of sludge with the natural zeolite or as precipitate from the treatment of industrial wastewater with the natural zeolite and coagulants, is suitable for safe deposition, since the fixation of the hazardous components in the micro/nano-pores of the HEU-type zeolite, as well as the meso- and macro-porous of natural zeolite, prevents their leaching by the rain water, protecting thus the quality of soils, surface and ground waters.